Autobiographical Memory: A Clinical Perspective - Urbanowitsch, Nadja; Gorenc, Lina; Herold, Christina J.; Schröder, Johannes (Frontiers in Behavioral Neuroscience, 2013)
Autobiographical memory (ABM) comprises memories of one’s own past that are characterized by a sense of subjective time and autonoetic awareness. Although ABM deficits are among the primary symptoms of patients with major psychiatric conditions such as mild cognitive impairment (MCI) and Alzheimer Disease (AD) or chronic schizophrenia large clinical studies are scarce. We therefore summarize and discuss the results of our clinical studies on ABM deficits in the respective conditions. In these studies ABM was assessed by using the same instrument – i.e. the Erweitertes Autobiographisches Gedächtnis Inventar (E-AGI) – thus allowing a direct comparison between diagnostic groups. Episodic ABM, especially the richness of details was impaired already in MCI and in beginning AD. Semantic memories were spared until moderate stages, indicating a dissociation between both memory systems. A recency effect was detectable in cognitively unimpaired subjects and vanished in patients with AD. A similar pattern of deficits was found in patients with chronic schizophrenia but not in patients with major depression. These autobiographical memory deficits were not accounted for by gender, or education level and did not apply for the physiological ageing process in otherwise healthy elderly. In conclusion, ABM deficits are frequently found in AD and chronic schizophrenia and primarily involve episodic rather than semantic memories. This dissociation corresponds to the multiple trace theory which hypothesized that these memory functions refer to distinct neuronal systems. The semi-structured interview E-AGI used to discern ABM changes provided a sufficient reliability measures, moreover potential effects of a number of important confounders could be falsified so far. These findings underline the relevance of ABM-assessments in clinical practice.